Criminal Law Enforcement Policy Against Convicted Corruption Offenders Continuously at the Denpasar District Court - Nahak, Simon (Indonesia Strategic Sustainability, 2025)
Purpose:The purpose of this paper is to analyze the politics of applying criminal sanctions against convicted corruption offenders on an ongoing basis and the legal consequences for perpetrators and victims of corruption in the Denpasar District Court.Methodology:The research method used is a collaboration between the normative juridical method and the empirical juridical method, with a quantitative and qualitative approach. Data was collected through in-depth interviews with perpetrators and victims of corruption. Then, an analysis of internal policy documents was conducted, as well as a survey of victims of extortion by convicted criminals.Findings:The results of the writing show that although there are regulations governing efforts to eradicate Corruption Crimes, there are still legal loopholes in their application that perpetrators of Corruption Crimes can exploit. This writing finds that legal protection education for victims and perpetrators is an important step in improving the political system of law enforcement that needs to be taken to strengthen legal protection.Implication:The output of this paper is expected to provide practical recommendations for perpetrators and victims to raise awareness and compliance with the law and to deter convicts from repeating their actions. Furthermore, the results of this paper can be used as a reference for better legal policies in protecting victims of extortion of corruption crimes in a sustainable manner with perpetrators to obtain justice, certainty, and legal benefits.